The Impact of Liquidity, Profitability And Activity Ratio To The Probability Of Default For Banking Companies Listed in Indonesia Stock Exchanges For The Period 2006 To 2012 - William Tjong; Herlina Lusmeida (UBL, 2013)
The purposes of this study is to examine the probability of default for banking companies listed in Indonesian Stock Exchange (IDX) for the period from 2006 to 2012. A high probability of default in the future have worried the companies and public. Therefore several urgent and important actions need to be taken to improve the performance of these listed companies. Several measures which might be related to performance could be liquidity, profitability and activity ratio to examine the performance of these companies.The population of this study is all the banking companies listed in IDX for the period of 2006 until 2012. To evaluate banksâ probability of default, we use some sample of banks by using Altmanâs approach. The result shows Altmanâs Z score ratio for almost banks in A category still have ratio under 1.11. Bank that has Z-Score </= 1.11 indicate that the bank in A category are in financial distress and has high risk. This study shows that the Z-Score of the companies doesnât always indicate about the existence of the companiesconsistenly.